1139. Novel Formulation SUBA-Itraconazole Prophylaxis in Patients With Hematological Malignancy or Undergoing Allogeneic Stem Cell Transplantation: Follow-up Survival Data. (26th November 2018) - Lindsay, Julian; Sandaradura, Indy; Wong, Kelly; Arthur, Chris; Stevenson, William; Kerridge, Ian; Fay, Keith; Coyle, Luke; Greenwood, Matthew
Abstract: Background: Despite the advantageous spectrum of activity of itraconazole, it is rarely used as a prophylactic agent due to limited bioavailability and intolerance of the conventional formulation. After the development of a novel formulation SUBA-itraconazole® (SUper BioAvailability), we undertook a study to assess therapeutic levels, safety, tolerability, and IFI rates of this novel formulation when compared with the conventional itraconazole liquid in patients undergoing allogeneic hematopoietic stem cell transplantation or in hematological malignancy patients. Methods: Following a single-centre, prospective study of SUBA–itraconazole 200 mg BID vs. conventional liquid itraconazole 200 mg BID, the SUBA–itraconazole group was assessed 1-year postallogeneic stem cell transplant for incidence of IFI and survival. Results: A total of 57 patients (29 SUBA–itraconazole and 30 liquid-itraconazole) were assessed. Therapeutic concentrations were achieved significantly more quickly in the SUBA–itraconazole group; median of 6 days vs. 14 ( P < 0.0001). At day 10, therapeutic concentrations were achieved in 69% of the SUBA–itraconazole group vs. 21% ( P < 0.0001). The mean trough serum concentrations at steady state of SUBA–itraconazole were significantly higher, with less interpatient variability (1, 577 ng/mL, CV 35%) vs. (1, 218 ng/mL, CV 60%) ( P < 0.001). There were 2 (7.5%) treatment failures in the SUBA–itraconazole group, both due to cessation of therapy for mucositis, compared with 7 (23.3%) treatment failures in the liquid-itraconazole group, due to subtherapeutic levels (five), mucositis (one), and gastrointestinal intolerance (one) ( P = 0.096). There was one confirmed IFI in the SUBA–itraconazole treatment failure group defined by a blood culture that yielded yeast; however, this was after the cessation of SUBA–itraconazole for mucositis. No other probable/possible IFIs were observed. After 1 year postallogeneic stem cell transplant in the SUBA–itraconazole group, there were two deaths (10%) due to disease progression and no further IFIs were reported. Conclusion: The use of the SUBA–itraconazole formulation was a safe and effective prophylactic agent. It was associated with more rapid attainment of therapeutic levels with less interpatient variability when compared with conventional liquid itraconazole. Disclosures: J. Lindsay, Mayne Pharma: Consultant, Consulting fee.